Resilinsi Kesejhteraan Psikologis Singel Mother Pasca Kematian Suami Studi Kasus Fenomenologi di Desa Momojiu Kabupaten Pulau Morotai - Suryani Hi Umar; Hamima Parati; Arni Zuhairini A Sibua (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Women’s psychological resilience may be threatened. This can be a burden for a woman who becomes a single mother following her husband’s death not due to divorce or other factors, but as a result of death or an accident. In line with the research focus, this study employs a descriptive qualitative approach using a phenomenological case study design, with 12 single mothers selected through purposive sampling. Data sources consisted of primary data obtained directly from the research subjects through in-depth interviews, as well as secondary data in the form of documentation and supporting records. The research instrument was an interview guide, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the death of a husband triggers profound emotional distress and a decline in psychological well-being, which is closely intertwined with a financial crisis. The burden of dual roles amid economic fluctuations in the local market—particularly the copra market became a major obstacle for single mothers, as this market constitutes their primary source of income. Nevertheless, the research subjects were able to effectively build resilience through their desire to secure a better future for their children as an internal motivator, supported by external factors such as family support and solidarity from neighbors. as well as the use of government programs. The conclusion of this study is that, although the death of a husband triggers severe psychological and economic vulnerability, single mothers’ resilience is successfully built through the optimization of internal motivation related to their children’s future, as well as social support from family, neighbors, and the government.